Is Anybody Listening? Using Participatory Methods to Co-Create an Impact Measure for Nurse education. - Janet M Garner; Susan McClenaghan; Steph Holmes; Angela Melling; Ernie Mallen; Rajendra Tayya (Journal of Participatory Research Methods)
Few impact measures in healthcare services and education are developed in full co-production with service users, patients and carers. This study aimed to address that gap. Service user and carer (patient and public) involvement in health and social care education is internationally recognised as crucial in helping to develop person-centred future professionals. The problem of how to ‘measure’ the impact of their involvement has become a dominant theme in the published literature in this field in recent years. Service users and carers also seek validation and assurance of their commitment and evidence to show they are making a difference. The drive towards co-production in education necessitates taking a fresh approach to evaluating the impact of involvement in higher education contexts and utilising the finite resource of service users and carers in the most effective way. This four-staged doctoral study utilised participatory action research (PAR) methods to develop a measure of impact which could be used to evaluate the impact of public involvement in nurse education at a UK university. This article describes the early stages of this process which included a scoping study and qualitative data collection. It is beyond the scope of this article to include a description of the later development and testing of the impact measure. We co-created a schedule of questions to explore views and perspectives using semi-structured interviews and focus groups to gather initial items for the measure. We hoped this would be useful to professionals developing and evaluating new approaches for pre-registration nurse education. Emphasis was given to service user and carers’ priorities throughout, in terms of appreciating their inputs and motivating future involvement in curriculum development. This article includes reflections from the participatory group members which were shared throughout the study; we believe these contribute to the critical appraisal of PAR research. We will publish a full description of the development and testing stages of the measure in a later article.